International Integration of Equity Markets and Contagion Effects - Cashin, Paul (IMF Working Papers; Working Paper, 1995)
This paper investigates empirically the degree of international integration of industrial and emerging country equity markets. It analyzes two issues: first, the extent to which equity prices have tended to move similarly across countries and regions in the long run; and second, the strength of cross-country 'contagion' effects. The paper's findings suggest that both intra-regional and inter-regional linkages across national equity markets have strengthened in recent years. In addition, using impulse response functions, the paper shows that cross-country contagion effects of country-specific shocks dissipate in a matter of weeks while contagion effects of global shocks take several months to unwind themselves.